Measuring Systemic and Climate Diversity in Ontario’s University Sector - Piche, Pierre Gilles (Canadian Journal of Higher Education, 2015)
This article proposes a methodology for measuring institutional diversity and applies it to Ontario’s university sector. This study first used hierarchical cluster analysis, which suggested there has been very little change in diversity between 1994 and 2010 as universities were clustered in three groups for both years. However, by adapting Birnbaum’s (1983) diversity matrix methodology to Ontario’s university sector, the author appears to have found a decrease in systemic diversity (differences in the type of institution and size of institution; Birnbaum, 1983) and climate diversity (differences in campus environment and culture; Birnbaum, 1983) between 1994 and 2010. Policy implications resulting from this study are also considered.